The African Challenge and its aftermath: Colonial legacies and the (re)making of the international legal order - (:unkn) unknown (My University, 2023)
Africa occupies a paradoxical position in International Relations scholarship. Political turmoil and violent conflicts on the continent have fueled the discipline’s revamping since the 1990s. Yet: Africa remains construed as disconnected from modern History. Law and legal institutions in particular still conjure the image of a legal vacuum. Against this representation, this chapter questions the entanglement between knowledge and imperialism in International Relations scholarship. Combining Global History with political sociology of law and lawyers, it opens a research agenda to trace the interconnectedness between legal developments across Africa and the Global North. It suggests that lawyers – their social characteristics, professional strategies and political mobilizations – are an entry-point to highlight transformations of the state and the historicity of globalization on the continent in the longue durée. This underscores that it is in these so-called African peripheries that major legal, political and economic revolutions, past and present, are at play.
Keywords: African Research